Differential cross sections for electron impact excitation of molecular hydrogen using the momentum-space multichannel optical method*Project supported by the National Natural Science Foundation of China (Grant Nos. 11447158 and 11404223). (20th February 2016) - Wang 王, Yuan-Cheng 远成; Ma 马, Jia 佳; Zhou 周, Ya-Jun 雅君
Abstract: In the present work, the momentum-space multichannel optical method is employed in four-state close-coupling calculations to study the electronic excitation of H2 molecules by electron-impact. Particularly, differential cross sections for the, , and transitions are reported. Comparison is made with the available experimental and theoretical results.